Face à l’École : les oscillations de mères de familles populaires - Chloé Riban (Recherches en Éducation)
In poor areas, where public policies are implemented in the education field, many projects aim at bringing parents closer to schools. In the schools studied in this ethnographic study, mothers are usually the ones who respond to these requests, by participating in school events and helping with homeworks. However, their busy everyday life and often difficult personnal situations sometimes prevent them from fully participating in school events and helping their children. If they trust the school, as a given, we observe that silent waverings define the relationships between mothers and teachers : their involvement sometimes hides muted tensions. Meeting the teachers is indeed a risk and has an emotionnal cost, which precipitates the use of various tactics. The difficulties their children may face (for learning or behavior), sometimes provoke attemps from the school to normalize their maternal attitudes, which may call into question the way these mothers raise their children at home. Yet, their maternal role is central to their identity, stemming from a naturalized vision of childcare. Their waverings in the relationship and the minimization of the disagrements appear then as a usefull behavior, intended to preserve a sort of balance, in which they are able to preserve their identities as mothers.